2018
DOI: 10.1038/s41598-018-26631-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling in the Prefrontal Cortex: Putative Mechanisms for the Cognitive Effects of Adolescent High Fat Feeding

Abstract: The medial prefrontal cortex (mPFC), master regulator of higher-order cognitive functions, is the only brain region that matures until late adolescence. During this period, the mPFC is sensitive to stressful events or suboptimal nutrition. For instance, high-fat diet (HFD) feeding during adolescence markedly impairs prefrontal-dependent cognition. It also provokes multiple changes at the cellular and synaptic scales within the mPFC, suggesting that major transcriptional events are elicited by HFD during this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 98 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the premature reduction in miR-19a/b-3p, miR-29a/c-3p, and miR-34 caused by repeated alcohol exposure could result in altered neurogenesis during puberty that would be potentially irreversible. Similar to our study, Lobouesse and colleagues recently demonstrated that consumption of a high fat diet during adolescence significantly altered 38 miRs in the prefrontal cortex, a brain region important for mediating cognitive and executive functions [47]. In that study, miRs regulating genes important for axon guidance were significantly affected, suggesting that neuronal connections between functionally aligned brain regions could be disrupted during adolescent brain development.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the premature reduction in miR-19a/b-3p, miR-29a/c-3p, and miR-34 caused by repeated alcohol exposure could result in altered neurogenesis during puberty that would be potentially irreversible. Similar to our study, Lobouesse and colleagues recently demonstrated that consumption of a high fat diet during adolescence significantly altered 38 miRs in the prefrontal cortex, a brain region important for mediating cognitive and executive functions [47]. In that study, miRs regulating genes important for axon guidance were significantly affected, suggesting that neuronal connections between functionally aligned brain regions could be disrupted during adolescent brain development.…”
Section: Discussionsupporting
confidence: 89%
“…Other than gene regulation via transcription factors, additional complexity of regulation can proceed via post-transcriptional regulation by microRNAs (miRNA), a family of small non-coding RNAs that regulate gene function by inhibiting the expression of their target mRNAs. miRNAs play important roles in regulation of different cellular and subcellular functions and are recognized as modulators of dendritic and synaptic maturation and synaptic activity, which in turn modify cognitive performance 17 . Interestingly, a high fat diet can modulate expression of miRNAs, such as miR-690, miR-30e, miR-10a-5p, miR-21a-3p, miR-511-3p, miR-690 or miR-8112, in mouse brain elucidating the contribution of microRNAs in cognitive dysfunction induced by diet 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed that lipotoxic injury regulates the expression of a number of microRNAs including up-regulation of mir-678 and mir-210. Mir-678 is known to be regulated by a high-fat diet [ 13 ]. Mir-210 has been shown to be up-regulated in the hippocampus and increase cognitive dysfunction in a rat model of vascular dementia (VD) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-fat diets can modulate the expression of genes related to neuronal projections and synaptic transmission corresponding to significant deterioration of neurite morphology and cognition [ 12 ]. In addition to changes in the expression of protein-coding genes, diets rich in lipids can modulate the expression of several miRNAs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%